(untitled) (Journal of Oriental Studies, 2021)
At different stages of Development, Society has different development goals, themes and priorities. China continues its socialist modernization, while maintaining Chinese specifics in choosing development paths and Planning Development Strategies. At different stages of development, China set different development goals and was guided by different development concepts. In his opening speech to the Nineteenth Party Congress on October 18, 2017, Xi Jinping noted the creation of the fully mature xiaokang (小康社会) society as the first of the four strategies of the «new era of socialism with Chinese characteristics», which official translators translate as «moderately prosperous society». One of the main tasks of a mature society is the development of human capital. At this stage of China’s development, people’s development is at the forefront. To achieve this goal, five development concepts were proposed. These concepts cover the areas of economy, political and spiritual culture, education and science, i.e. innovation, openness, environmental development, coordination and shared development. This article describes the concept of shared development, which plays an important role in the in the formation of Xiaokang society, attempts are made to reveal the main aspects of the concept of shared development, to show its practical application and prospects in the construction of socialism with Chinese characteristics in the new era. Key words: China, development, CPP, socialism, xiaokang, shared development, Datong.